(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied and calculated the fraction of empty semiconductor nanocrystals which controls the quantum yield as a function of the average number of donors per nanocrystal and the nanocrystal size. We have shown that if donor reached the critical value of 1.8 there are no empty nanocrystals in nanocrystal array due to electron redistribution between nanocrystals and consequently photoluminescence vanishes. The relative intensity of the photoluminescence is strongly correlated with the transport properties of these array. Which provides information about the redistribution of the charges between nanocrystals affecting both quantum yield of photoluminescence of an array of nanocrystals and its hopping conductivity. We have found that empty nanocrystals became extinct and photoluminescence was quenched abruptly at an average number of donors per nanocrystal. It turned out that doping resulted in transport properties which were typical for disordered semiconductors. The number of donors in different nanocrystals was random. In the ground state of the nanocrystal array many nanocrystals were charged. The charged nanocrystals leaded to the random coulomb potential and to the coulomb gap in the density of localized electron states that determined variable range of hopping conductivity. It was also found that an array of small nanocrystals due to the quantuization-gap induced redistribution of electrons among nanocrystals. The obtained results were found in good agreement with previous results.